Oculomotor Deficits and Symptom Severity Are Associated With Poorer Dynamic Mobility in Chronic Mild Traumatic Brain Injury - D'Silva, Linda J.; Chalise, Prabhakar; Obaidat, Sakher; Rippee, Michael; Devos, Hannes (Frontiers in Neurology, 2021)
Oculomotor deficits, vestibular impairments, and persistent symptoms are common after a mild traumatic brain injury (mTBI); however, the relationship between visual-vestibular deficits, symptom severity, and dynamic mobility tasks is unclear. Twenty-three individuals (mean age 55.7 ± 9.3 years) with persistent symptoms after mTBI, who were between 3 months to 2 years post-injury were compared with 23 age and sex-matched controls. Oculomotor deficits (depth perception, near-point convergence, baseline visual acuity (BLVA), perception time), vestibular deficits (dynamic visual acuity in the pitch and yaw planes), dynamic mobility measured by the Functional Gait Assessment (FGA), and symptoms measured by the Post-Concussion Symptom Scale (PCSS) and Dizziness Handicap Inventory (DHI) were compared between groups. Participants with mTBI had poorer performance on the FGA (p<0.001), higher symptom severity on the PCSS (p<0.001), and higher DHI scores (p<0.001) compared to controls. Significant differences were seen on specific items of the FGA between individuals with mTBI and controls including walking with horizontal head turns (p<0.001), walking with vertical head tilts (p<0.001), stepping over an obstacle (p=0.004), tandem gait (p=0.003), walking with eyes closed (p=0.003), and stair climbing (p<0.001). After adjusting for age in multiple regression analysis, significant associations of BLVA (p=0.04) and DHI score (p=0.048) with FGA score were found. Dynamic balance deficits persist in chronic mTBI and may be addressed using multifaceted rehabilitation strategies to address oculomotor dysfunction, post-concussion symptoms, and perception of handicap due to dizziness.